Forebrain Ischemia Triggers GABAergic System Degeneration in Substantia Nigra at Chronic Stages in Rats. (17th October 2010) - Lin, B.; Levy, S.; Raval, A. P.; Perez-Pinzon, M. A.; DeFazio, R. A.
Abstract : The long-term consequences of forebrain ischemia include delayed Parkinson's syndrome. This study revealed delayed neurodegeneration in the substantia nigra 8 weeks after 12.5 minutes of global ischemia in rat brain. Following neuronal loss of 30–40% in central and dorsolateral striatum at day 3, neuronal damage in the substantia nigra (SN) was assessed at 4–8 weeks using immunohistochemistry for glutamate decarboxylase 67 (GAD67), vesicular GABA transporter (VGAT), and calretinin (CR). At day 56, the optical density of GAD67-, but not VGAT-, immunoreactivity in substantia nigra pars reticulata (SNR)—significantly decreased. CR-neurons concentrated in substantia nigra pars compacta (SNC) were reduced by 27% from day 3 (n = 5 ) to day 56 (n = 7, ANOVA, p < .01 ). Movement coordination was impaired at day 56, as evaluated using beam-walking test (time-to-traverse5.6 ± 1.2 sec versus11.8 ± 5.4 sec; sham versus ischemia, p < .05, n = 5, and 7, resp.). Our results demonstrate delayed impairment of the GABAergic system components in SN and associated with movement deficits after global ischemia.